(untitled) (Південний архів (історичні науки), 2023)
The article is devoted to the Kuris family charitable activities in the Odessa Charitable Women’s Society in the first half of the XIX century. In the context of charity development trends in the South of modern Ukraine in the first half of the nineteenth centurythe beginning and formation of one of the most developed charitable women’s organizations of Odessa of that time – the Odessa women’s charitable society is investigated. The origins of the Society, the main directions and features of its activities, sources of funding are analyzed. Particular attention is paid to the organization of the orphanage by the Society and the education of its residents. Among the special achievements of the Society are the church building, the establishment of a garden, the organization of its own trade and production activities, due to which the development of the Society was carried out and its work was ensured. The purpose of the research is to study the role of representatives of the Kuris clan in the charitable activities of the Odessa Women’s Charitable Society in the first half of the 19th century. Research methods. During the research, the comparative-historical method, the historical-systematic method, the method of analysis and synthesis of historical sources were used. Results and conclusions. Based on the study, conclusions were drawn about the Kuris family charity. Among the military, social, economic heritage of the family a special place was devoted to collecting, philanthropy and charity. Not only the glorious men of the Kuris family, Ivan Onufriyovych Kuris and Ivan Irakliyovych Kuris, made an indisputable contribution to the development of the South of modern Ukraine, but also the women of the Kuris family were engaged in education and had an active social life. From the Kuris family, in addition to Kateryna Ivanivna, the wife of Ivan Onufriyovych Kuris, the Society included her daughters-in-law Elizaveta Lvivna and Lyubov Stanislavivna. All of them took part in organizing the supply of food and medicine to citizens in need, accommodation of homeless people to cheap apartments, assisted in public work organization, participated in the upbringing of homeless children. Based on the study of the life of LyubovStanislavovna Kuris, the beginning of her charitable activity was analyzed, which she had very active all her life. Participation in the work of the Odessa Women’s Charitable Society was only the first step towards this woman’s charitable deeds – educational activities, founding a school at her own expense, participation in other charitable organizations.